2015
DOI: 10.1016/j.bbabio.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial-targeted antioxidant, MitoQ, increases liver mitochondrial cardiolipin content in obesogenic diet-fed rats

Abstract: Cardiolipin (CL), a unique mitochondrial phospholipid, plays a key role in several processes of mitochondrial bioenergetics as well as in mitochondrial membrane stability and dynamics. The present study was designed to determine the effect of MitoQ, a mitochondrial-targeted antioxidant, on the content of liver mitochondrial membrane phospholipids, in particular CL, and its fatty acid composition in obesogenic diet-fed rats. To do this, twenty-four 6week old male Sprague Dawley rats were randomized into three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 44 publications
3
30
1
1
Order By: Relevance
“…Thus, the increase of CL content during the 1st weeks of HFHFR diet might preserve mitochondrial bioenergetic function. In accordance with that, we and others (12,37,38) have reported increased CL content with HFHFR diet. Increase in CL content may be driven by an increase in overall CL synthesis or a decrease in CL degradation.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the increase of CL content during the 1st weeks of HFHFR diet might preserve mitochondrial bioenergetic function. In accordance with that, we and others (12,37,38) have reported increased CL content with HFHFR diet. Increase in CL content may be driven by an increase in overall CL synthesis or a decrease in CL degradation.…”
Section: Discussionsupporting
confidence: 92%
“…CL oxidation impairs mitochondrial complex I activity, which is implicated in neurotoxicity and apoptosis in 1‐methyl‐4‐phenyl‐1,2,4,6‐tetrahydropyridine (MPTP) mice (Perier et al, ). In direct support of a causative role of CL peroxidation in the development of PD, mitochondrial‐targeted antioxidants attenuate pathogenesis and protect CL from oxidative damage in mouse models of neurodegenerative diseases (Fouret et al, ; McManus, Murphy, & Franklin, ; Skulachev et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Feeding rats with a high-fat diet and MitoQ for 8 weeks effectively increased the expression of cardiolipin synthase gene and its level in the liver mitochondria. 87 The MitoQ showed noticeable improvement in the manifestations of metabolic syndrome in rats fed a high-fat diet. 88 Furthermore, previous studies demonstrated the antiapoptotic effect of MitoQ, which was mediated through the inhibition of cytochrome c release and caspase-3 activation.…”
Section: Anthocyanidinsmentioning
confidence: 97%